KALIGRAFI SEBAGAI SENI BUDAYA ISLAM DAN ARSITEKTUR - Dea Dwi Atika; Mita Atiiqah Br Ginting (Jurnal Ekshis, 2024)
The art of calligraphy has become an integral part of Islamic art and architecture, reflecting the richness of cultural and spiritual values in Islamic society. This research aims to explore the influence and role of calligraphy in shaping Islamic cultural identity through art and architectural design. In this study, we conducted a comprehensive literature review on calligraphy as an Islamic cultural art and architecture. The results show that calligraphy is not only a decorative element, but also a means to convey religious and philosophical messages to Muslims. The use of calligraphy in Islamic architecture creates a spiritual atmosphere and distinctive visual beauty. Calligraphy also plays a role in strengthening Islamic cultural identity and enriching the heritage of Islamic fine arts. It is hoped that this research can be a valuable reference source for researchers, artists, and architects in understanding and appreciating the richness of calligraphic art in the context of Islamic culture and architecture.